COACHING BEHAVIORAL ASPECTS THROUGH PHYSICAL EDUCATION : LITERATURE REVIEW - Raffiandy Alsyifa Putra; Phil Yanuar Kiram; padli padli; Fiky Zarya (Faculty of Sport Science, Universitas Negeri Yogyakarta, 2022)
The focus of the data that will be displayed in the literature of this review is at least aimed at describing the education, physical activity, character building of children in the school period. The research method used is literature review by following the literature review procedure. Using keywords on google scholar